Tonometry as an outcome measure for the treatment of Dupuytren’s disease. - Ball, C; Izadi, D; Nanchahal, J (International Dupuytren Society, 2015)
Hypothesis: Early DD can be treated in a variety of ways, including Intralesional steroid injections and radiotherapy, but there are no objective ways of assessing disease regression. The current literature relies on clinical examination of palmar nodule consistency. An objective non-invasive measure of tissue pliability that can be used as an outcome measure to effectively compare clinical interventions is required. Method: Tonometry has been used clinically to evaluate tissue hardness of cutaneous scars and lymphoedema. The resistance of tissues to compression is measured using a durometer, a hand-held mechanical gauge which is rested against the patient’s skin. Patients with Dupuytren’s disease and healthy volunteers were recruited prospectively to a clinical trial to determine whether tonometry can be used to distinguish between the hardness of palmar nodules in patients with Dupuytren’s disease and palmar skin of healthy volunteers at an equivalent site. Ethical approval was obtained and all recruited patients gave informed written consent. Tissue hardness was measured using a durometer and scored from 0-100 with 100 being the hardest reading possible. Two independent assessors measured all patients using an agreed standardised protocol to minimise inter-observer variability. Each assessor was blinded to the score recorded by the other. Three measurements were taken and the mean score recorded. Results: Thirty seven participants were recruited to the study: 25 patients with Dupuytren’s disease and 12 healthy volunteers. The healthy volunteers were matched for gender and age to patients with Dupuytren’s disease. The ages of the healthy volunteer (mean ± SEM, 61.4 ± 3.1 years) and the patients with Dupuytren’s disease (64.5 ± 2.1) were similar, as was the ratio of male to female patients in both groups (3:1). Dupuytren’s disease, affected hands only (mean ± SEM) Healthy volunteers, both hands (mean ± SEM) P value Tonometry Mean 58 ± 8 Mean 32 ± 3 <0.0001 Inter-observer reliability was high as assessed by calculation of the intraclass correlation coefficient of 0.96 (95% confidence intervals 0.942 to 0.967) p <0.0001. Conclusion: • The hardness of palmar nodules in patients with Dupuytren’s Disease can be measured by a rapid, simple, and inexpensive tonometry test • Further research is needed to evaluate the use of tonometry as an objective outcome measure for patients with early Dupuytren’s disease